(untitled) (Research, Society and Development, 2017)
Indigenous education is becoming a priority to be dealt with in Higher Education. Therefore, efforts are oriented towards newly nourishing inclusive proposals for education; for them to take cultural diversity on and generate quality learning processes while also promoting the vindication of the right towards a culturally-relevant education for indigenous populations. Hence, the article sets forth an analysis of the pedagogical practice by an indigenous cabécar teacher, which unveils elements and cultural aspects that constitute valuable input to be considered in teacher education proposals. This research took place in the educative community of Sharabata, which is part of the High Chirripó Cábecar Indigenous Territory, which in turn is located in the province of Cartago in the Central American country of Costa Rica. The current research was conducted as a case study. Obtained results now create curricular content that responds to socio-cultural, linguistic and natural needs and characteristics of the cabécar culture. The present research recovers oral communication and the value of words, of learning by imitation, cosmovision as cultural heritage and the importance of recognizing mother languages in originary populations. It is forewarned that, though handled under the discourse of cultural displacement, practical and ritualistic practices still persist, all of which must be acknowledged and valued in school by young people in order for culture as ancestral heritage to be prolonged. It is given the mentioned situations where education must be made present; as a fight towards respect, inclusion and the strengthening of originary cultures. In that sense and in order to achieve cultural relevance, the process of the construction of knowledge with children must be inserted in its historical, social and cultural context, for which knowledge, experience and the practice of cabécar cosmovision is transcendental. As part of cultural relevance, respect and value are recognized in regards to the cultural knowledge that every boy or girl possesses, so that new knowledge is not conflictive or overwriting of that which has already been learned as cultural heritage. Instead, such knowledge is only amplified or complemented.